تقييم الأنواع الشجرية وأثرها في عناصر الفرش العمراني في شارع حلب بمدينة اللاذقية (Latakia University Journal -Biological Sciences Series, 2017)
تتحدد القيمة الجمالية والبيئية لأي شارع إلى حد بعيد باختيار النوع الشجري المناسب وبعلاقة أشجاره المزروعة مع مختلف العناصر الهندسية للشارع . تلعب أشجار الشوارع دوراً هاماً في تشكيل النسيج العمراني والجمالي للمدينة , كما تعمل على تعزيز الجوانب المادية والبيئية والثقافية للمدينة. تناول البحث تحليل الصفوف الشجرية لشارع حلب ودراسة علاقة أشجاره مع المكونات الهندسية الإنشائية والخدمية له. كما تمَّ تقدير الحالة المثالية للأنواع الشجرية المزروعة بهذا الشارع باستخدام معادلة لي وآخرون (Li et al,2011). أظهرت نتائج البحث وجود تقطعات بارزة في الصفوف الشجرية للشارع .كما بيَّنت أن الصفوف الشجرية في شارع حلب تحتوي على أربعة أنواع شجرية Ficus nitida L., Jacaranda mimosaefolia L. ,.S Eucalyptus rostrata ., Melia azedrach L , مما سبب تشوهاً لجمالية الشارع وتواضعاً في الغنى النباتي لهذه الصفوف . كما كشفت نتائج البحث عن تدني القيمة لدرجة مثالية بعض الأنواع المستخدمة بالشارع كالجاكرندا الذي حاز /6,22/درجة , في حين كانت هذه القيمة مقبولة في نوع التين اللامع /7/درجة ونوع الأوكاليبتوس المنقاري 7.28 درجة ونوع الازدرخت 7.53 درجة من أصل /10/ درجات. فيما يخص علاقة الأشجار ببعض العناصر الهندسية للشارع , أظهرت النتائج عدم مراعاة الأبعاد القياسية بين الأشجار المزروعة والعناصر الخدمية. أثرت هذه الحالة سلباً على القيمة الجمالية لواجهات الأبنية والمحلات التجارية وعلى درجة وضوح اللوحات الإرشادية والإعلانية من جهة , كما تزايدت المخاطر على المشاة والآليات نتيجة حجب رؤية الإشارات المرورية وتداخل تيجان الأشجار مع أعمدة الإنارة والكهرباء من جهةٍ أخرى .The aesthetic and environmental values of a street are greatly influenced by the selection of an appropriate arboreal species and the relation between its planted trees with the different engineering elements of a street . Street trees play a significant role in forming the architectural and aesthetic texture of the city. They, forther more, enhance material, environmental and cultural aspects of the city. This paper aimes to analyze arboreal rows in HALAB Street and to study their relation with the service and structural engineering components Of that street . Moreover, the optimal situation of these street trees was evaluated using (Li et al, 2011) equation.Results of this paper revealed prominent breaks in the arboreal rows, and that these rows contain four tree species (Jacaranda mimosaefolia Don., Ficus nitida L., Eucalyptus rostrata S., Melia azedrach L.), which served to furnish the street with monotonic beauty and humility in botanic diversity. Findings showed decrease in the optimal value of the two used botanic species where (Jacaranda) attained a mark of 6.22/10 and (Ficus nitidia) 7/10 and (Eucalyptus) 7.28/10 and (Melia) 7.53/10. Corresponding to the relation of trees to some street engineering elements, results indicated inobservance of standard dimensions between planted trees and service elements. which negatively influenced the aesthetic and position value of buildings’ and stores’ facets and guiding signs and billboards on the one hand, and risk increase on pedestrians and vehicles due to blocking vision of traffic signs and overlap of tree crowns with electricity and lighting posts on the other hand.